Agronomic performance of five rapeseed varieties grown for biodiesel in the northeast of Portugal - Rodrigues, M.A. (2014)
Rapeseed is an important crop for several European countries and for many others such as Canada and China. Rapeseed oil may have several industrial uses (Sonntag, 1995) and shows excellent properties for the manufacture of biodiesel (Körbitz, 1995). Rapeseed oil may also present high food quality, namely CANOLA (Canadian Oilseed Low-Acid) and European “double-zero” varieties (erucic acid in the oil and glucosinolates in rapeseed cake). World production of rapeseed has quadrupled in the past three decades (FAO, 2013). In Europe the increase in acreage has also been remarkable. Portugal is one of the few European countries where rapeseed is not yet extensively grown. However, field trials carried out in the country (Ferreira, 2009, Rodrigues et al. 2010, Rodrigues et al., 2011) have given good indications on its ecological potential to produce rapeseed if cultivated in the autumn/winter growing season. In the European market there are rapeseed varieties of high vernalisation requirements, suitable for cultivation of rapeseed as an autumn/winter crop, and varieties of smaller vernalisation requirements for cultivation as a spring/summer crop (Guerrero, 1999). In regions benefitting from a Mediterranean climate, rapeseed should be cultivated as an autumn/winter crop in order to mitigate drought problems during spring. In rainfed cropping systems of the Mediterranean region, rapeseed could be an interesting crop to increase the number of the few species that can be included in the crop rotations. In these rotations, rapeseed could be a good preceding crop for wheat since it left a nitrogen-rich residue in the soil (Marquard and Walter, 1995; Arlesa 2011a). If rapeseed is included in irrigated crop rotations, it may validate a double-cropping system, where rapeseed could be grown in winter previously to a second crop in the summer season. The present work aims to assess the potential of five rapeseed cultivars to be grown in rainfed conditions in Northeast of Portugal. These cultivars are being marketed in Spain by Arlesa-Euralis Company and were already grown with relative success in Spain close to the border with Portugal.